2018
DOI: 10.1007/s00167-018-4843-4
|View full text |Cite
|
Sign up to set email alerts
|

Short- to mid-term outcomes of anatomic MCL reconstruction with Achilles tendon allograft after multiligament knee injury

Abstract: Type IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
1
16
0
4
Order By: Relevance
“…Consensus is lacking, however, on treatment of KDIIIM injuries. Good results have been reported with both non-operative and operative treatments of medial side injuries and bicruciate ligament reconstruction in the acute phase [ 3 , 7 , 22 , 34 , 38 ]. There is a risk of residual valgus laxity with conservative treatment of distal MCL avulsion injury [ 42 ] or in the presence of an MCL Stener-like lesion [ 5 , 40 ], and operative treatment is recommended for a grade-III distal tear or tibial avulsion of the MCL [ 2 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consensus is lacking, however, on treatment of KDIIIM injuries. Good results have been reported with both non-operative and operative treatments of medial side injuries and bicruciate ligament reconstruction in the acute phase [ 3 , 7 , 22 , 34 , 38 ]. There is a risk of residual valgus laxity with conservative treatment of distal MCL avulsion injury [ 42 ] or in the presence of an MCL Stener-like lesion [ 5 , 40 ], and operative treatment is recommended for a grade-III distal tear or tibial avulsion of the MCL [ 2 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported satisfactory outcomes after reconstruction of the MCL in MLKI. 32,49,50 LaPrade and Wijdicks 36 reported on 28 patients who underwent anatomic PMC reconstruction of the MCL and POL with concurrent cruciate or bicruciate ligament reconstruction. Patients had clinical improvement in their mean subjective IKDC scores from 44 to 76 postoperatively and all 28 patients had resolution of side-toside instability at 2 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that knee dislocation grades were significantly correlated with postoperative outcome measures. 50 One of the main concerns in treating MLKI with medialsided injuries is the development of postoperative arthrofibrosis and joint stiffness, especially when treated in the acute phase. 23,24 Stannard et al reported on outcomes after surgical treatment of medial-sided injuries in multiligament injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally a higher age at time of injury is considered as worse prognostic factor, albeit data is lacking for patients with multi-ligament injured knees. Most studies on multi-ligament injured knees did not investigate the influence of age on clinical outcomes (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Hence, it was the purpose of this study to perform a single-centre retrospective study and compare the long-term outcomes of younger and older patients.…”
mentioning
confidence: 99%